The Influence of Inquiry Learning Models Based on Audio Visual Media on Student Learning Outcomes in Science and Technology Subjects in Class IV Elementary Schools - Sianturi, Nelli Kristina; Juliana, Juliana; Silaban, Patri Janson; Lumbanraja, Bogor; Ambarwati, Nova Florentina (JURNAL PAJAR (Pendidikan dan Pengajaran), 2025)
This study aims to determine the influence of the AudioVisual Media-based Inquiry learning model on the learning outcomes of grade IV students at UPT SD Negeri 068008 Damar, Medan Tuntungan District, Medan City for the 2023/2024 Academic Year. The research method used is an experimental method with a type of quantitative research and the number of samples in this study is 25 students based on the boring sampling technique (total sampling). The data on the Inquiry learning model was obtained from questionnaires distributed to students and student learning outcomes were obtained from the students' Pretest and Posttest scores in the 2023/2024 academic year.The students' learning outcomes showed that the average score of the Pretest grade IV students was 65.12 while the average score of the Posttest was 88.96. Furthermore, the results of hypothesis testing showed 6,944 while it was 2,060. So it is evident that Ho was rejected and Ha was accepted. Through the t-test, it can be concluded that there is a significant positive influence between the  Audio-Visual Media-based Inquiry learning model on student learning outcomes in the science and science subject class IV UPT SD Negeri 068008 Medan Tuntungan for the 2023/2024 Academic Year.